Serum folate and homocysteine levels in patients with obsessive-compulsive disorder - Atmaca, M; Tezcan, E; Kuloglu, M; Kirtas, O; Ustundag, B (Blackwell Publishing, 2005)
Previous studies have shown that folate deficiency, increased homocysteine, impaired metylation have been identified in depressive disorder. Recently, growing research has resulted in the biological association between obsessive-compulsive disorder (OCD) and affective disorders. Therefore, in the present study it was evaluated whether or not folate and homocysteine levels changed. Serum folate and homocysteine concentrations were measured in 23 patients with OCD and in same number of controls. In addition, all patients were assessed by Yale-Brown Obsession Compulsion Scale (Y-BOCS). Serum folate values were significantly lower in OCD patients than in controls, while homocysteine concentrations were higher in patients compared with controls. Serum folate values were significantly and negatively related to Y-BOCS scores. Total serum homocysteine concentrations were positively correlated to Y-BOCS scores and the duration of illness. There was a trend toward a negative correlation between the concentrations of serum folate and homocysteine. In conclusion, we identified that a group of patients with OCD might have folate deficiency, higher homocysteine levels and probable impaired metylation and monoamine metabolism.
Keywords: folate; homocysteine; metylation; obsessive-compulsive disorder